Diagnosis of breast lesions: fine-needle aspiration cytology or core needle biopsy? A review. Issue 4 (29th October 2011) - Willems, S M; van Deurzen, C H M; van Diest, P J
Abstract : Diagnosis of breast lesions is routinely performed by the triple assessment of a specialised surgeon, radiologist and pathologist. In this setting, fine-needle aspiration cytology (FNAC) and core needle biopsy (CNB) are the current methods of choice for pathological diagnosis, both with their specific advantages and limitations. Evidence-based literature discussing which of both modalities is preferable in breast lesion diagnosis is sparse and there is no consensus among different specialised breast cancer centres. This study reviews FNAC and CNB for diagnosing breast lesions, comparing methodological issues, diagnostic performance indices, possibilities for additional prognostic and predictive tests and cost effectiveness. Overall, CNB achieved better sensitivity and specificity especially in those lesions that were not definitively benign or malignant, non-palpable and/or calcified lesions. Although FNAC is easier to perform, interpretation requires vast experience and even then, it is more often inconclusive requiring additional CNB. The authors conclude that overall CNB is to be preferred as a diagnostic method.